Problematika Pengasuhan Single Parent dalam Pendidikan Moral Keagamaan bagi Anak di Keluarga - Sari, Suci Aulia; Fauziah, Puji Yanti; Elfiadi, Elfiadi (JURUSAN PENDIDIKAN GURU PENDIDIKAN ANAK USIA DINI, 2023)
The purpose of this study was to find out how the problems of single-parent parenting in religious moral education for children in the family. To achieve this goal, researchers used field research methods (field research) which are qualitative. The research was conducted in May 2021 at Uteun Geulilnggang Village, Dewantara District, North Aceh Regency. Data collection techniques used are through interviews, observation, and documentation. To test the validity of this research data, the researcher used triangulation. While the analysis of research data includes: data reduction, data presentation, and conclusion. The results obtained from the study concluded that there were two problems in parenting faced by single parents, namely the first socio-economic problems in the form of problems affecting children's religious moral education and the second problems of children's religious moral education in the family itself. Socio-economic problems include aspects of providing a living, caring for children, and paying attention to child psychology. In this socio-economic problem, the majority of single parents only fulfill one aspect. The results of the study suggest that being a single parent is not an obstacle in parenting, good single parents are single parents who can provide balanced time, income, and attention for children.